INCREASING THE PROFITABILITY OF CITIZENS THROUGH CLARIIDAE CULTIVATION VEGETABLE PLANTS WITH AQUAPONIC TECHNIQUES IN CISEENG VILLAGE, BOGOR REGENCY - A Hadian Pratama H Hamzah; Nurhasanah Nurhasanah; Rini Yayuk Priyati; Sri Harijati; Ludivica Endang Setijorini (Jurnal PkM (Pengabdian kepada Masyarakat), 2022)
Ciseeng Village is located in Ciseeng District, Bogor Regency. Product The main advantage of Ciseeng Village is in the agriculture and animal husbandry sector, but in this village it is often there is a drought which makes activities hampered so that it has an impact on the needs of the local economy. In the agricultural and livestock sectors, there are still many village shortages, one of which is the drought factor and the flood factor is because the village This is only found in a few places that have water irrigation. Through service activities It is hoped that this solution will be resolved by the community. Implementation of Devotion to This community aims to provide guidance and training for clariidae  farming and vegetables with aquaponics techniques, with this the community can not only cultivating clariidae but can also grow a variety of vegetables in the same bucket used as a container for clariidae farming Budikdamper, this is one of the future food solutions that can be developed for meet the food needs of the community, especially the needs of animal protein and vegetables. This solution was carried out considering the limited land for fish cultivation and starting to decrease water quality and quantity, Budikdamper becomes a one option that can be applied to address future food solutions.